High-level expression and purification of soluble form of human natural killer cell receptor NKR-P1 in HEK293S GnTI- cells - Bláha, Jan; Kalousková, Barbora; Skořepa, Ondřej; Pažický, Samuel; Novák, Petr; Vaněk, Ondřej (Protein expression and purification, 2017)
Human natural killer receptor protein 1 (NKR-P1, CD161, gene klrb1) is a C-type lectin-like receptor of natural killer (NK) cells responsible for recognition of its cognate protein ligand lectin-like transcript 1 (LLT1). NKR-P1 is the single human orthologue of the prototypical rodent NKR-P1 receptors. Naturally, human NKR-P1 is expressed on the surface of NK cells, where it serves as inhibitory receptor; and on T and NKT cells functioning as co-stimulatory receptor promoting secretion of IFNγ. Most notably, it is expressed on Th17 and Tc17 lymphocytes where presumably promotes targeting into LLT1 expressing immunologically privileged niches. We tested effect of different protein tags (SUMO, TRX, GST, MsyB) on expression of soluble NKR-P1 in E. coli. Then we optimized the expression construct of soluble NKR-P1 by preparing a library of expression constructs in pOPING vector containing the extracellular lectin-like domain with different length of the putative N-terminal stalk region and tested its expression in Sf9 and HEK293 cells. Finally, a high-level expression of soluble NKR-P1 was achieved by stable expression in suspension-adapted HEK293S GnTI- cells utilizing pOPINGTTneo expression vector. Purified soluble NKR-P1 is homogeneous, deglycosylatable, crystallizable and monomeric in solution, as shown by size-exclusion chromatography, multi-angle light scattering and analytical ultracentrifugation.
Keywords: NK cells; buňky Th17; buňky NK; Bioreactors; Lectins, C-Type; Killer Cells, Natural; lidé; Humans; LLT1; klrb1; Receptors, Cell Surface; Th17 Cells; NK Cell Lectin-Like Receptor Subfamily B; HEK293 buňky; ligandy; NKR-P1; receptory buněčného povrchu; lektinové receptory NK-buněk - podrodina B; CD161; lektiny typu C; HEK293; HEK293 Cells; Ligands; Escherichia coli; bioreaktory